Optimasi Algoritma K-Means Menggunakan Metode Elbow dalam Pengelompokan Penyakit Demam Berdarah Dengue (DBD) di Jawa Barat - Dea Amelia; Tesa Nur Padilah; Asep Jamaludin (Peneliti.net, 2022)
Dengue hemorrhagic fever (DHF) is an acute febrile infectious disease that usually occurs in tropical and subtropical areas of the world and is caused by a virus transmitted by the Aedes mosquito, namely Aedes aegypti and Aedes albopictus. Dengue fever is one of the endemic diseases that almost occurs throughout the world. Indonesia is the country with the highest dengue fever cases in Southeast Asia. One of the provinces with the most cases of dengue fever is West Java. Every year cases of dengue fever have increased and decreased, so cases cannot be controlled properly. This must be a concern for the West Java Government in handling this Dengue Fever disease. To help the Government of West Java, this research conducted a grouping of dengue fever in West Java in 2016-2021. This research uses the Knowledge Discovery in Database (KDD) method. The algorithm used is k-means clustering with the help of the elbow method to get the optimal number of clusters, which is 2 clusters. Cluster 0 with low category consists of 22 regions, and cluster 2 with high category consists of 5 regions. The result of silhouette coefficient evaluation is 0.689 with standard structure criteria